Rodin and the French Genius : 100 Years of Figurative Sculpture. - Le Marchant, Michael; Bruton Gallery Limited, Somerset; Noortman & Brod, New York (Somerset : Bruton Gallery Limited, 1983)
Carpeaux, Jean-Baptiste ; Dalou, Jules Aimé ; Rodin, Auguste ; Bourdelle, Emile Antoine ; Wlérick, Robert ; Buxin, Stephan ; Carton, Jean
Bruton Gallery, Somerset, 1 October - 29 October 1983 ; Noortman & Brod, New York, 18 November 1983 - 14 January 1984
kunstcatalogus
Keywords: Frankrijk